Prévalence de la dépression majeure chez les arthritiques des populations canadiennes: étude comparative entre anglophones majoritaires et francophones en situation linguistique minoritaire - Fotsing, Salomon (Can J Public Health, 2013)
OBJECTIVE: Mental health and arthritis have been recognized as major public health issues. Francophone minority status has now been acknowledged as a health determinant. The objective of this study was to determine the prevalence of major depression among adults with arthritis in Francophone minority populations compared to the Anglophone majority. METHODS: Secondary analysis of the CCHS (merger of 2003 (cycle 2.1), 2005 (Cycle 3.1), 2007 (cycle 4.1), 2008 and 2009) excluding Quebec residents. The language variable was constructed using an existing algorithm which combines maternal tongue, language of conversation, language of interview, and preferred language. Major depression was defined according to the DSM IV. Presence or absence of arthritis was a self-reported variable. The prevalence and odds ratios for depression in people with arthritis were calculated and adjusted for various factors (socio-economic, social isolation, access to health services). RESULTS: The study identified 159,426 Anglophones and 10,658 Francophones. Among the participants with arthritis (27%), the prevalence of depression in Francophones and Anglophones was 8.5% and 8.4%, respectively. In men, Anglophones were more at risk for depression than Francophones: OR 2.36 (95% CI: 2.07-2.70) vs. OR 1.87 (95% CI: 1.20-2.91). This trend was not observed in women. CONCLUSION: In our sample of people with arthritis, depression seems to affect more particularly the English-speaking men, however given the small sample size, we need to be cautious in our conclusions.